Applying the Self-Determination Theory to explain the link between perceived parental overprotection and perfectionism dimensions. (April 2023) - Casale, Silvia; Fioravanti, Giulia; Ghinassi, Simon
Abstract: Previous research offers evidence that parental overprotection explains – at least in part – the development of certain individual differences relevant to psychological maladjustment, including perfectionism. The current study aims to build upon this evidence by adopting the Self-Determination Theory as a theoretical framework for understanding the psychological processes that might explain the effect of parental overprotection (PO) on different features of perfectionism. Three-hundred and nineteen Italian participants ( F  = 73.7 %; M age  = 31.51 ± 13.04 years) were recruited and administered the Italian versions of the Parental Bonding Instrument, the Basic Psychological Need Satisfaction and Frustration Scale, the Big Three Perfectionism Scale, the Perfectionistic Self-Presentation Scale, and the Perfectionism Cognition Inventory. Structural equation modeling supported the hypothesized mediating effect of needs frustration in the above-mentioned links, especially when it comes to trait perfectionism and perfectionistic cognitions. Competence frustration played the most relevant role in explaining how parental overprotection might contribute to perfectionism dimensions. The current study provides evidence of a potential critical developmental pathway to perfectionism, with implications for clinical practice.